PROBLEMATIK BATAS ANTARA SASTRA LOKAL, SASTRA NASIONAL, DAN SASTRA GLOBAL - Ratih Tri Pertiwi (BASA Journal of Language & Literature, 2021)
Abstract: This study aims to expose the vagueness of the boundaries between local, national, and global literature. This research is literature research. This study presents evidence that limiting the boundaries between local, national, and global literature is problematic. The results of this study show that local, national, and global literature presents a intersecting and overlapping. Local literature can be said to be national literature because of some of its characteristics, national literature can also be said to be global literature because of some of its rubber, and vice versa. Based on the results of the study, it can be concluded that the most important thing is not the categorization of that type of literature, but the utilization of the literary work. Keywords: Problematic Boundaries, Literature, Local, Naional, Global